298 Feasibility of A Dietary Sodium Reduction Intervention Using mHealth Technology to Improve Adherence in Hypertensive Patients - Jisook Ko; Jing Wang (Journal of Clinical and Translational Science, 2022)
OBJECTIVES/GOALS: Despite the large body of evidence concerning the effects of dietary interventions on blood pressure, trials have often reported poor adherence to sodium restriction. We implemented the Sodium Watcher Program-Hypertension (SWPH) program using digital self-monitoring. The purpose of this study was to determine the feasibility of the SWPH program. METHODS/STUDY POPULATION: The SWPH is a pilot two-arm, 2-month randomized controlled trial that enrolls adults with hypertension. The intervention group received personalized feedback on dietary sodium intake and BP and the control group participants received usual care for hypertension. Both groups participated in digital self-monitoring of daily diet and BP over 8 weeks. The primary outcomes were adherence to dietary sodium intake as captured by 24-hour urinary sodium excretion and BP at baseline and at the 2-month follow-up. Feasibility assessment included adherence to dietary sodium intake monitoring and in-home BP monitoring measured by the percentage of days that participant logged their food intake and in-home BP. The preliminary effect on the outcome variables was tested by using a repeated-measures analysis of variance. RESULTS/ANTICIPATED RESULTS: In this feasibility study, we included data from 12 participants (n=9 SWPH, n=3 control) who completed all phases of the study. The patients median age was 56.5 years and 70% were female. The mean baseline BP was 142.7/87.5 mmHg. The mean 24-hour urine sodium of 4853.0 mg (SD=1639.9 mg) with 80% having 24-hour urine sodium >2300 mg at baseline. SWPH group had lower systolic (baseline 142.4 mmHg vs follow-up 124.1 mmHg, p<0.001), diastolic (baseline 87.1 mmHg vs follow-up 77.5 mmHg, p<0.05) BP, and 24-hour urine sodium (baseline 3790.4 mg vs 2609.7 mg, p<0.05) compared with control group. Compared with the control group, the SWPH group had significantly more eligible days of digital food log usage (control 80.0% vs intervention 98.2%, p<0.01) and in-home BP monitor usage (control 77.6% vs intervention 94.6%, p<0.01). DISCUSSION/SIGNIFICANCE: Millions of Americans remain in need of effective interventions to manage their hypertension. Innovative and accessible strategies to sustain a low sodium diet intervention are needed for the majority of individuals not following the low sodium diet. By leveraging digital self-monitoring, a low sodium diet program was feasible and in reducing BP.